Gaps in Medical Students' Competencies to Deal With Intimate Partner Violence in Key Mozambican Medical Schools - Manuel, Beatriz; Roelens, Kristien; Tiago, Armindo; Keygnaert, Ines; Valcke, Martin (Frontiers in Public Health, 2019)
Purpose: This research seeks to identify the gaps in competencies designed to help medical students to deal with Intimate Partner Violence (IPV) in key Mozambican medical schools curricula. Method: A survey was administered to 3rd- and 6th-year medical students (N387), enrolled in five medical schools in Mozambique. The instrument focused on mapping students’ perceived mastery of their knowledge, skills and attitudes related to IPV. Results: In total, 387 medical students (RR 66%) participated in the survey. The overall mean perceived mastery of IPV competence was 36.18 (SD=24.52) for knowledge, 32.01 (SD=27.37) for skills and 43.47 (SD=27.58) for attitudes. Though 6th-year students reported a significantly higher mastery level, it is still below a mastery-learning benchmark of 80%. Conclusions: Medical students report critically low levels in their mastery of IPV- related competencies. This implies a need for a more comprehensive approach to developing knowledge, skills and attitudes to deal with the victims of IPV.